Response essay: standpointing global communication - Qiu, Jack Linchuan (2024)
This response essay discusses the need to study global communication (GC) from different standpoints, the pitfalls therein, and strategies to overcome them. It starts with two reflections: from China, and on the uneven landscape of GC research and pedagogy around the world, where obstacles and opportunities co-exist. This is followed by a critique on comparative analysis that can be used productively, or it can lead to atheoretical comparativism that reproduces problems of the status quo. Two examples are given to showcase how critical GC pedagogies of power and counter-power can be carried out.